Trauma, suffering, and resilience - de Casas Soberón, Elena; Berliner, Peter (Psyke & Logos, 2011)
The article discusses the challenge of using a conceptual framework to understand traumatic stress and still be open to listening to the stories of suffering, of lamentation, grief, hope, and the values of people being oppressed by organised violence. The complexity of responses to the losses caused by the violent oppression is shown through a presentation of the autobiographic book “Cerezas” by Aurora Correa.